Folate Receptor‐Mediated Delivery of Cas9 RNP for Enhanced Immune Checkpoint Disruption in Cancer Cells. Issue 2 (18th November 2022) - Lin, Yi; Wilk, Ulrich; Pöhmerer, Jana; Hörterer, Elisa; Höhn, Miriam; Luo, Xianjin; Mai, Hongcheng; Wagner, Ernst; Lächelt, Ulrich
Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system offers great opportunities for the treatment of numerous diseases by precise modification of the genome. The functional unit of the system is represented by Cas9/sgRNA ribonucleoproteins (RNP), which mediate sequence‐specific cleavage of DNA. For therapeutic applications, efficient and cell‐specific transport into target cells is essential. Here, Cas9 RNP nanocarriers are described, which are based on lipid‐modified oligoamino amides and folic acid (FolA)‐PEG to realize receptor‐mediated uptake and gene editing in cancer cells. In vitro studies confirm strongly enhanced potency of receptor‐mediated delivery, and the nanocarriers enable efficient knockout of GFP and two immune checkpoint genes, PD‐L1 and PVR, at low nanomolar concentrations. Compared with non‐targeted nanoparticles, FolA‐modified nanocarriers achieve substantially higher gene editing including dual PD‐L1/PVR gene disruption after injection into CT26 tumors in vivo. In the syngeneic mouse model, dual disruption of PD‐L1 and PVR leads to CD8+ T cell recruitment and distinct CT26 tumor growth inhibition, clearly superior to the individual knockouts alone. The reported Cas9 RNP nanocarriers represent a versatile platform for potent and receptor‐specific gene editing. In addition, the study demonstrates a promising strategy for cancer immunotherapy by permanent and combined immune checkpoint disruption. Abstract : For therapeutic genome editing, efficient and cell‐specific transport of the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system into target cells is desirable. Here, folic acid‐modified Cas9 ribonucleoprotein nanocarriers are presented, which mediate enhanced gene modification in folate receptor expressing cancer cells and are utilized for disruption of two immune checkpoint genes as a cancer immunotherapy approach.